2017
DOI: 10.1002/lio2.65
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss as a risk factor for dementia: A systematic review

Abstract: ObjectivesTo review evidence of hearing loss as a risk factor for dementia. Data Sources: PubMed Review methods: A systematic review was conducted using the PubMed database using the search terms (hearing loss OR presbycusis) AND (dementia OR cognitive decline). Initially, 488 articles were obtained. Only those studies evaluating an association between hearing loss and incident dementia or cognitive decline were included in the analysis. This resulted in 17 articles which were thoroughly evaluated with conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
204
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(217 citation statements)
references
References 52 publications
(337 reference statements)
10
204
0
3
Order By: Relevance
“…Even though no causal link has been established between hearing loss and dementia, many epidemiological studies have shown hearing loss as a risk factor for developing dementia. 14,15 Our study showed significantly higher risk of dementia among the middle old age group [OR 2.39 (1.00-5.70)]. Studies conducted in Kerala, Tamil Nadu and other parts of Northern India also reported increasing age as a nonmodifiable risk factor of dementia.…”
Section: Independent Risk Factors Of Dementiasupporting
confidence: 55%
“…Even though no causal link has been established between hearing loss and dementia, many epidemiological studies have shown hearing loss as a risk factor for developing dementia. 14,15 Our study showed significantly higher risk of dementia among the middle old age group [OR 2.39 (1.00-5.70)]. Studies conducted in Kerala, Tamil Nadu and other parts of Northern India also reported increasing age as a nonmodifiable risk factor of dementia.…”
Section: Independent Risk Factors Of Dementiasupporting
confidence: 55%
“…16,17 Although the implications of UHL in adults is not well studied, recent data show poorer cognitive function in adults with bilateral HL. [7][8][9][10][11][12] Given the minimal risk of hearing aid use, but the potential benefit, we recommend public health education about the importance of testing for and treating UHL in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, significant efforts have been devoted to identifying a link between hearing loss and cognitive dysfunction . A recent systematic review identified 17 studies, each of which suggested at least a weak correlation between age‐related hearing loss and dementia . If hearing loss contributes to cognitive decline, then hearing restoration may represent a modifiable risk factor to ameliorate cognitive decline.…”
Section: Introductionmentioning
confidence: 99%